2000
DOI: 10.4049/jimmunol.164.4.1658
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: B Cells Promote CD8+ T Cell Activation in MRL-FaslprMice Independently of MHC Class I Antigen Presentation

Abstract: Spontaneous CD8+ T cell activation in MRL-Faslpr mice is B cell dependent. It is unclear whether this B-dependent activation is mediated by direct Ag presentation via MHC class I proteins (i.e., cross-presentation) or whether activation occurs by an indirect mechanism, e.g., via effects on CD4+ cells. To determine how CD8+ T cell activation is promoted by B cells, we created mixed bone marrow chimeras where direct MHC class I Ag presentation by B cells was abrogated while other leukocyte compartments could exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Future examination of corresponding B-cell subsets and BAFF levels in emerging murine models possessing phenotypic changes that closely mirror those of cGVHD patients will yield important information. 54 Identification of immune targets in cGVHD in further investigations is also required to determine whether IgG produced by activated B cells contributes to end organ damage by aiding in cross-presentation to T cells, 55,56 forming immune complexes that deposit in tissue, 57 or through binding to functional receptors. 18 Naive B lymphopenia in patients with active cGVHD appeared to begin during the first year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Future examination of corresponding B-cell subsets and BAFF levels in emerging murine models possessing phenotypic changes that closely mirror those of cGVHD patients will yield important information. 54 Identification of immune targets in cGVHD in further investigations is also required to determine whether IgG produced by activated B cells contributes to end organ damage by aiding in cross-presentation to T cells, 55,56 forming immune complexes that deposit in tissue, 57 or through binding to functional receptors. 18 Naive B lymphopenia in patients with active cGVHD appeared to begin during the first year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our MRL-Fas lpr mice that were IL-10 deficient had expansion of conventional CD3 ϩ CD4 ϩ B220 Ϫ and CD3 ϩ CD8 ϩ B220 Ϫ T cells, also suggesting a regulatory role of this cytokine in controlling the number of conventional T cells, including those that promote autoantibody production and renal disease. Indeed, recent studies with B cell-deficient or autoantibody-deficient MRL-Fas lpr mice (39,40) have suggested that disease can occur in the absence of B cells and autoantibodies; i.e., T cells presumably can promote disease independently of B cell help. However, the finding that MRL-Fas lpr IL-10 Ϫ/Ϫ mice had T cell expansion suggests that IL-10 can regulate T cell expansion apart from Fas-Fas ligand interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anti-dsDNA antibodies identifies patients at risk of lupus nephritis, consistent with experimental evidence that these antibodies have a causative role in GN when deposited as immune complexes in the kidney. However, B cell-deficient but not antibody-deficient mice are protected from lupus nephritis, indicating that cellular functions of B cells also contribute to disease pathogenesis (149,150). In addition to glomerular lesions, lupus nephritis is characterized by inflammation and scarring of the renal interstitium, which predicts progression to renal failure.…”
Section: Role In Gnmentioning
confidence: 99%